Schrankiana chacoensis sp. nov. (Nematoda: Atractidae) from Leptodactylus bufonius Boulenger, 1894 (Anura: Leptodactylidae) from Argentina - Gonzalez, Cynthya Elizabeth (2014)
Here we describe a new atractid nematode, Schrankiana chacoensis sp. nov., from the large intestine of Leptodactylus bufonius (Anura: Leptodactylidae), from Chaco Province, Argentina. This is the first atractid nematode described for L. bufonius. The new species is distinguished from the remaining species of the genus by its cephalic morphology: S. chacoensis sp. nov. possesses four large papillae on the lips (two on the dorsal lip and one on each subventral lip) without any other small papillae (present in the remaining Schrankiana species) and forked amphids; by having a shorter vagina; tips of the lateral alae located well anterior to the anus in both sexes, one additional pair of postcloacal papillae compared with other species, and a "fringe" in the posterior and anterior margins of the excretory pore. Schrankiana chacoensis sp. nov. represents the eighth species assigned to the genus. A key to the species of the genus is provided